Heat treatment process of armored twisted pair cable for self-sufficient neutron detector of nuclear power plant

CN122918310APending Publication Date: 2026-10-16JIANGXI CABLE +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610764169.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0002]自给能中子探测器是核反应堆堆芯测量系统中的关键部件,其通过发射体在中子作用下产生电流信号,无需外部供电即可实现中子通量测量,探测器信号的稳定传输依赖于铠装双绞线的长期可靠性,目前,用于该环境的铠装电缆通常采用镍基合金(如Inconel600)作为导体与护套材料,并在其中填充陶瓷绝缘材料(如氧化铝、氧化镁),然而,在反应堆堆芯的恶劣工况(温度可达350℃以上、高剂量辐照、长期振动)下,电缆材料的微观组织易发生劣化,导致机械强度下降、绝缘性能衰减、信号传输不稳定,甚至因材料疲劳引发失效

Benefits of technology

1、提升高温力学性能:通过将镍-铬-铁基合金管坯进加热固溶处理、将镍-铬-铁基合金线材进行加热并保温处理和退火处理,使Inconel600合金获得均匀细小的晶粒组织,室温抗拉强度稳定在≥560MPa,屈服强度≥250MPa,延伸率≥35%,且在350℃高温下强度衰减率小于15%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918310A_ABST
    Figure CN122918310A_ABST
Patent Text Reader

Abstract

The present application provides a kind of nuclear power plant self-powered neutron probe armored twisted pair heat treatment process, this process includes: nickel-chromium-iron-based alloy pipe blank is heated to solid solution temperature in inert atmosphere environment, and keeps warm, the nickel-chromium-iron-based alloy pipe blank after keeping warm is rapidly cooled to room temperature, obtains shell material;Nickel-chromium-iron-based alloy wire rod is heated in inert atmosphere environment, and keeps warm, the nickel-chromium-iron-based alloy wire rod after keeping warm is cooled to room temperature, obtains core wire material;By heating solid solution treatment to nickel-chromium-iron-based alloy pipe blank to obtain shell material, nickel-chromium-iron-based alloy wire rod is treated by medium temperature annealing to obtain core wire material, so that alloy element is fully solid solution, carbide is completely dissolved, and the grain of nickel-chromium-iron-based alloy pipe and nickel-chromium-iron-based alloy wire rod is refined.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nuclear power detection and signal transmission technology, and in particular to a heat treatment process for armored twisted-pair wires of a self-sufficient neutron detector for nuclear power plants. Background Technology

[0002] Self-powered neutron detectors are key components in nuclear reactor core measurement systems. They generate current signals through the emitter under the influence of neutrons, enabling neutron flux measurement without external power supply. The stable transmission of the detector signal depends on the long-term reliability of the armored twisted-pair cable. Currently, armored cables used in this environment typically use nickel-based alloys (such as Inconel 600) as conductor and sheath materials, filled with ceramic insulation materials (such as alumina and magnesium oxide). However, under the harsh operating conditions of the reactor core (temperatures can reach above 350°C, high-dose radiation, and long-term vibration), the microstructure of the cable material is prone to deterioration, leading to decreased mechanical strength, reduced insulation performance, unstable signal transmission, and even failure due to material fatigue.

[0003] In existing technologies, the heat treatment of alloy materials mostly adopts conventional solution treatment or annealing processes, but these have not been optimized for the characteristics of the multi-layer composite structure of armored twisted pairs. For example, although patents such as CN110764130A mention hot drawing, the description of the early heat treatment process of the material is insufficient, resulting in a rapid decrease in insulation resistance and large fluctuations in mechanical properties of the finished cable at high temperatures. In addition, the difference in thermal expansion coefficients between the insulation material and the metal shell is large, which easily generates interfacial stress during temperature cycling, reduces the bonding strength, and affects the sealing performance and long-term stability.

[0004] Therefore, there is an urgent need to develop a graded heat treatment process for the Inconel 600 alloy shell and core wire of armored twisted pair cables. By precisely controlling the heating temperature, holding time, cooling rate and atmosphere, the material grain size can be optimized, internal stress can be eliminated, high-temperature performance can be improved, and the metal-insulation layer interface bonding can be enhanced, thereby comprehensively improving the service life and signal fidelity of the cable in the core environment. Summary of the Invention

[0005] In view of the above situation, the main objective of this invention is to propose a heat treatment process for armored twisted-pair cables of self-powered neutron detectors in nuclear power plants, so as to solve the above-mentioned technical problems.

[0006] This invention proposes a heat treatment process for armored twisted-pair cables of self-powered neutron detectors in nuclear power plants, the method comprising the following steps: Step 1: Heat the nickel-chromium-iron-based alloy tube blank to the solution temperature in an inert atmosphere and hold it at that temperature. After holding at that temperature, cool it to room temperature to obtain the outer shell material. Step 2: Heat the nickel-chromium-iron-based alloy wire in an inert atmosphere and keep it at that temperature to allow the nickel-chromium-iron-based alloy wire to recrystallize and refine the grains, thus obtaining the nickel-chromium-iron-based alloy wire after heat preservation. Cool the nickel-chromium-iron-based alloy wire after heat preservation to room temperature to obtain the core wire material. Step 3: Calcining alumina powder or nano alumina powder to remove impurities, and adding yttrium oxide as a sintering aid for sintering. After sintering, the powder is cooled in the furnace to promote the densification of alumina and obtain an insulating material. Step 4: Twist the core wire material to obtain stranded core wire material. Insert the stranded core wire material into the outer shell material and fill the annular gap between the outer shell material and the core wire material with insulating material to obtain a semi-finished cable. Step 5: Perform stress-relief annealing on the semi-finished cable and keep it warm. After keeping it warm, use a gradient cooling process to release these interface stresses in a gentler and more controllable way. After the gradient cooling process, cool it in the furnace to obtain the annealed semi-finished cable. Step 6: The annealed semi-finished cable is subjected to a drawing and diameter reduction process to compact the insulating powder and obtain the finished cable.

[0007] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Improved high-temperature mechanical properties: By heating and solution treating the nickel-chromium-iron-based alloy tube blank, and heating and holding the nickel-chromium-iron-based alloy wire and annealing it, the Inconel 600 alloy obtains a uniform and fine grain structure, with a room temperature tensile strength of ≥560MPa, a yield strength of ≥250MPa, an elongation of ≥35%, and a strength decay rate of less than 15% at 350℃.

[0008] 2. Enhanced high-temperature insulation stability: The heat-treated material and the insulation layer are tightly bonded at the interface. The insulation resistance of the finished cable can reach more than 1×10¹³Ω·m at 20℃ and can still maintain more than 5×10⁹Ω·m at 350℃, which is significantly better than conventional processes.

[0009] 3. Optimized radiation resistance: The uniform and fine grain structure is expected to reduce radiation damage sensitivity and extend the service life of the cable in strong radiation environments.

[0010] 4. Improve process consistency: Strict control of graded heat treatment parameters ensures the uniformity and stability of material properties in mass production.

[0011] 5. Improved long-term reliability: Effective stress-relief annealing significantly reduces residual stress inside the cable, making the product less prone to structural relaxation and insulation degradation in long-term thermal cycling and vibration environments.

[0012] Additional aspects and advantages of the invention will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by means of embodiments of the invention. Attached Figure Description

[0013] Figure 1 This is a schematic diagram of the Inconel 600 alloy microstructure of the armored twisted-pair wire heat treatment process for the self-powered neutron detector in nuclear power plants proposed in this invention.

[0014] Figure 2 This is a temperature-time qualitative diagram of the heat treatment process of the present invention. Detailed Implementation

[0015] Embodiments of the present invention are described in detail below. Examples of these embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0016] These and other aspects of the embodiments of the present invention will become clear from the following description and accompanying drawings. In these descriptions and drawings, some specific embodiments of the present invention are specifically disclosed to provide some ways of implementing the principles of the embodiments of the present invention; however, it should be understood that the scope of the embodiments of the present invention is not limited thereto.

[0017] This invention proposes a heat treatment process for armored twisted-pair cables of self-powered neutron detectors in nuclear power plants, which includes the following steps: Example 1: A heat treatment process for armored twisted-pair wires of a self-sufficient neutron detector in a nuclear power plant, the method comprising the following steps: Step 1: The nickel-chromium-iron-based alloy tube blank is heated to 1180℃ in an argon atmosphere using a high-frequency induction heating device and held at that temperature for 30 minutes to fully dissolve the alloying elements and the carbides (such as Cr23C6 precipitates) that are originally present in the alloy. Then, the nickel-chromium-iron-based alloy tube blank is sprayed with high-pressure argon gas for quenching and cooled to room temperature at a rate of 50℃ / s to obtain the shell material. The shell material has a supersaturated solid solution structure. Step 2: Heat the nickel-chromium-iron-based alloy wire to 880°C in an argon atmosphere to allow recrystallization and grain refinement. Hold the wire at this temperature for 15 minutes. Then, cool the wire to room temperature at a rate of 20°C / s using a water jacket to obtain the core material. The core material has a non-supersaturated solid solution microstructure. Step 3: Use alumina powder with a mass fraction of 99.5% and a purity of ≥99%. Calcinate the alumina powder at 800℃ for 1 hour. Then, add 0.5% yttrium oxide as a sintering aid and cool it in the furnace to promote alumina sintering densification, remove volatile impurities, and improve powder flowability and high-temperature insulation performance. Step 4: Twist the two core wires in a bidirectional symmetrical manner, with the twisting pitch set to 8 times the core wire diameter and the twisting tension controlled at 0.5N to obtain the twisted core wire material. Then, coaxially insert the twisted core wire material into the outer shell material and use a vibration filling method to fill the annular gap between the outer shell material and the core wire material with insulating material to achieve a filling density of over 70%. Step 5: Perform stress-relief annealing on the semi-finished cable. The annealing temperature is 300℃ and held for 1 hour. Then, the temperature is reduced to 250℃ at a rate of 10℃ / min and held for another 0.5 hours. Finally, the cable is cooled in the furnace to obtain the annealed semi-finished cable. Step 6: Perform a three-stage drawing process on the annealed semi-finished cable. Place the annealed semi-finished cable into the drawing die for continuous drawing, so that the total diameter reduction rate of the annealed semi-finished cable is 60%, the diameter reduction rate of the first drawing is 20%, the diameter reduction rate of the middle drawing is 35%, and the diameter reduction rate of the middle drawing is 17.5% each time, and the diameter reduction rate of the final drawing is 5%. The drawing speed is controlled at 5m / min. After each drawing, the cable is subjected to intermediate stress-relief annealing at a temperature of 950℃ for a holding time of 0.5h. After the drawing is completed, the insulating powder is compacted to a density of ≥85%, and the finished cable is obtained, which is denoted as A1.

[0018] It should be noted that the microstructure of the Inconel 600 alloy in the finished cable prepared in this embodiment is shown in the schematic diagram below. Figure 1 As shown.

[0019] Example 2: A heat treatment process for armored twisted-pair wires of a self-sufficient neutron detector in a nuclear power plant, the method comprising the following steps: Step 1: The nickel-chromium-iron-based alloy tube blank is heated to 1200℃ in a nitrogen atmosphere using a high-frequency induction heating device and held in the nitrogen atmosphere for 45 minutes to fully dissolve the alloying elements and the carbides (such as Cr23C6 and other precipitates) that are originally present in the alloy. Then, the nickel-chromium-iron-based alloy tube blank is sprayed with high-pressure nitrogen for quenching and cooled to room temperature at a rate of 65℃ / s to obtain the shell material. The shell material has a supersaturated solid solution structure. Step 2: Heat the nickel-chromium-iron-based alloy wire to 900°C in a nitrogen atmosphere to allow recrystallization and grain refinement. Hold the wire at this temperature for 22.5 minutes. Then, cool the wire to room temperature at a rate of 30°C / s using a water jacket to obtain the core material. The core material has a non-supersaturated solid solution microstructure. Step 3: Use 99.5% nano-alumina powder with a purity of ≥99% and calcine it at 900℃ for 1.5h. Then add 0.5% yttrium oxide as a sintering aid and cool it in the furnace to promote the densification of alumina sintering, remove volatile impurities, and improve the powder flowability and high-temperature insulation performance. Step 4: Twist the three core wires in a bidirectional symmetrical manner, with the twisting pitch set to 9 times the core wire diameter and the twisting tension controlled at 1.25N to obtain the twisted core wires. Then, coaxially insert the twisted core wires into the outer shell material and use a pneumatic filling method to fill the annular gap between the outer shell material and the core wires with insulating material to achieve a filling density of over 75%. Step 5: Perform stress-relief annealing on the semi-finished cable. The annealing temperature is 350℃ and the temperature is held for 1.5h. Then, the temperature is reduced to 250℃ at 10℃ / min and held for another 0.5h. Finally, the cable is cooled in the furnace to obtain the annealed semi-finished cable. Step 6: The annealed semi-finished cable is subjected to four-stage drawing. The annealed semi-finished cable is placed into the drawing die for continuous drawing, so that the total diameter reduction rate of the annealed semi-finished cable is 70%. The diameter reduction rate of the first drawing is 25%, the diameter reduction rate of the middle drawing is 35%, and the diameter reduction rate of the middle drawing is 17.5% each time. The diameter reduction rate of the last drawing is 10%. The drawing speed is controlled at 10 m / min. After each drawing, the cable is subjected to intermediate stress-relief annealing at a temperature of 1000℃ for a holding time of 1.25h. After the drawing is completed, the insulating powder is compacted to a density of more than 85%, and the finished cable is obtained, which is denoted as A2.

[0020] Example 3: A heat treatment process for armored twisted-pair wires of a self-sufficient neutron detector in a nuclear power plant, the method comprising the following steps: Step 1: The nickel-chromium-iron-based alloy tube blank is heated to 1220℃ in an argon atmosphere using a high-frequency induction heating device and held at that temperature for 60 minutes to allow the alloying elements and the carbides (such as Cr23C6 precipitates) in the alloy to dissolve completely. Then, the nickel-chromium-iron-based alloy tube blank is quenched by spraying high-pressure argon gas and cooled to room temperature at a rate of 80℃ / s to obtain the shell material. The shell material has a supersaturated solid solution microstructure. Step 2: Heat the nickel-chromium-iron-based alloy wire to 920°C in an argon atmosphere to allow recrystallization and grain refinement. Hold the wire at this temperature for 30 minutes. Then, cool the wire to room temperature at a rate of 40°C / s using a water-cooling jacket to obtain the core material. The core material has a non-supersaturated solid solution microstructure. Step 3: Use alumina powder with a mass fraction of 99.5% and a purity of ≥99%. Calcinate the alumina powder at 1000℃ for 2 hours. Then add 0.5% yttrium oxide as a sintering aid and cool it in the furnace to promote alumina sintering densification, remove volatile impurities, and improve powder flowability and high-temperature insulation performance. Step 4: Twist the four core wires in a bidirectional symmetrical manner, with the twisting pitch set to 10 times the core wire diameter and the twisting tension controlled at 2N to obtain the twisted core wire material. Then, coaxially insert the twisted core wire material into the outer shell material and use a vibration filling method to fill the annular gap between the outer shell material and the core wire material with insulating material to achieve a filling density of 80%. Step 5: Perform stress-relief annealing on the semi-finished cable. The annealing temperature is 400℃ and held for 2 hours. Then, the temperature is reduced to 250℃ at a rate of 10℃ / min and held for another 0.5 hours. Finally, the cable is cooled in the furnace to obtain the annealed semi-finished cable. Step 6: The annealed semi-finished cable is subjected to five-stage drawing. The annealed semi-finished cable is placed into the drawing die for continuous drawing, so that the total diameter reduction rate of the annealed semi-finished cable is 80%, the diameter reduction rate of the first drawing is 30%, the diameter reduction rate of the middle drawing is 35%, and the diameter reduction rate of the middle drawing is 17.5% each time, and the diameter reduction rate of the final drawing is 15%. The drawing speed is controlled at 15 m / min. After each drawing, the cable is subjected to intermediate stress-relief annealing at a temperature of 1050℃ for 2 hours. After the drawing is completed, the insulation powder is compacted to a density of more than 85%, and the finished cable is obtained, which is denoted as A3.

[0021] Comparative Example 1: The nickel-chromium-iron-based alloy tube was heated to 1050℃ and held for 30 minutes for solution treatment, followed by water quenching. The nickel-chromium-iron-based alloy wire was not subjected to intermediate annealing, and no stress-relief annealing or drawing densification was performed after assembly and filling.

[0022] Comparative Example 2: The nickel-chromium-iron-based alloy tube was subjected to a solution treatment at 1180℃, followed by air cooling at a rate of 20℃ / s. The nickel-chromium-iron-based alloy wire was subjected to intermediate annealing at 890℃ without stress relief.

[0023] To verify the effectiveness of this invention, performance tests and comparisons were conducted. The product performance of the above embodiments and comparative examples was tested according to GB / T 228.1-2021 (tensile properties) and GB / T 3048.5-2007 (insulation resistance), and the results are shown in Table 1. Meanwhile, the temperature-time relationship in the heat treatment process is as follows... Figure 2 As shown.

[0024] Table 1 Comparison of key performance characteristics of armored twisted-pair cables under different heat treatment processes

[0025] Performance Analysis: As can be seen from the data in Table 1, Embodiments 1 and 2 of the present invention are significantly superior to Comparative Examples 1 and 2 in all key performance indicators. The following is a detailed analysis from three dimensions: mechanical properties, insulation properties, and microstructure.

[0026] (I) Analysis of Mechanical Performance Improvement Comparative Example 1 only applied conventional 1050℃ solution treatment to the nickel-chromium-iron alloy tube, which failed to fully dissolve the carbides in the alloy. Furthermore, although subsequent water quenching achieved some supersaturation, the grain size of the nickel-chromium-iron alloy tube was only ASTM 4.5 grade, with coarse and uneven grains. This resulted in a room temperature tensile strength of 510 MPa, which decreased to 385 MPa at 350℃, a decrease rate as high as 24.5%. In the long-term service environment of a reactor core at 350℃, such a high strength degradation would significantly increase the risk of cable deformation and breakage.

[0027] Comparative Example 2 used a solution treatment at 1180℃ for the nickel-chromium-iron-based alloy tube, but air cooling at a rate of only 20℃ / s failed to effectively suppress the recrystallization of carbides at the grain boundaries, resulting in a grain size improvement of only 6.0 grade. Meanwhile, although the nickel-chromium-iron-based alloy wire underwent intermediate annealing at 890℃, stress-relief annealing was not performed, preventing the release of residual stress introduced during assembly and drawing. Consequently, the room temperature tensile strength increased to 545MPa, and the strength decay rate at 350℃ decreased to 18.3%, but this was still relatively high.

[0028] In contrast, Example 2 of this invention employs a 1200℃ solution treatment and a 60℃ / s rapid cooling process (high-pressure nitrogen spray) for the nickel-chromium-iron-based alloy tube blank, along with two stress-relief annealing treatments on the semi-finished cable. This ensures complete dissolution of the alloying elements and the complete dissolution of carbides, which are "frozen" in the matrix during rapid cooling, preventing grain boundary precipitation. Simultaneously, the 900℃ intermediate annealing of the nickel-chromium-iron-based alloy wire eliminates work hardening, refines the grain size of both the nickel-chromium-iron-based alloy tube and wire, achieving a final grain size of 7.5. The room temperature tensile strength is increased to 575 MPa, a 12.7% improvement compared to Comparative Example 1 and a 5.5% improvement compared to Comparative Example 2. More importantly, the strength decay rate at 350℃ is reduced to 14.8%, significantly lower than the 24.5% of Comparative Example 1 and 18.3% of Comparative Example 2.

[0029] Example 3 further employs a solution treatment at 1220℃, rapid cooling at 80℃ / s, and two stress-relief annealing treatments on the semi-finished cable. The grain size reaches grade 8.0, the room temperature tensile strength is 590MPa, and the strength decay rate at 350℃ is 13.6%. This indicates that the synergistic effect of high-temperature solution treatment, rapid cooling, and intermediate annealing is the key to improving high-temperature mechanical properties; without any one of these steps, such excellent performance cannot be achieved.

[0030] (II) Analysis of Insulation Performance Improvement Insulation resistance is a core performance indicator of armored twisted-pair cables in the reactor core environment. In Comparative Example 1, due to the lack of calcination pretreatment of the filler powder and the absence of stress-relief annealing and drawing densification, there are a large number of voids and impurities at the interface between the insulating powder and the metal. The room temperature insulation resistance is only 2.3×10¹² Ω·m. Due to the difference in thermal expansion coefficients between the metal and ceramic insulating materials, thermal stress is generated at the interface, leading to microcracks and peeling. At the same time, the mobility of residual impurity ions in the insulating powder increases at high temperatures. The combined effect of these two factors causes the insulation resistance to drop sharply to 8.2×10⁷ Ω·m, an attenuation of more than four orders of magnitude. This can lead to severe signal drift or even short circuits during nuclear power plant operation.

[0031] Although Comparative Example 2 underwent intermediate annealing of the core wire, the insufficient cooling rate of the outer casing resulted in uneven metal structure and high interfacial stress. Furthermore, the lack of stress-relief annealing led to poor interfacial bonding quality. Its room temperature insulation resistance increased to 5.1 × 10¹² Ω·m, but still dropped to 2.5 × 10⁸ Ω·m at 350℃, a decrease of approximately two orders of magnitude. Under long-term operation, this would still cause severe signal drift or even short circuits.

[0032] Embodiment 2 of the present invention significantly improves insulation performance through the following measures: 1. Pre-treatment of nano-alumina powder by calcination at 900℃ removes volatile impurities and adsorbed moisture, thereby improving the purity and flowability of the powder.

[0033] 2. After filling, the powder was drawn down to compact it, resulting in a density of over 85% and reducing porosity.

[0034] 3. Stress-relief annealing was performed at 350℃, followed by heat preservation. After heat preservation, a gradient cooling process was adopted to effectively release the residual stress at the metal-ceramic interface. This process allows for a smoother and more controllable release of the interface stress, avoiding the generation of new thermal stress due to rapid cooling. It also improves the dimensional stability and yield of the cable in subsequent drawing and diameter reduction processes, and enhances the interface bonding.

[0035] 4. The semi-finished cable after annealing is subjected to a drawing and diameter reduction process. After each drawing, the cable undergoes intermediate stress-relief annealing. By progressively compacting the insulating powder, high density and uniformity are achieved. The annealing after each drawing eliminates the processing stress step by step during the manufacturing process, resulting in a uniform microstructure and extremely low internal residual stress in the finished cable.

[0036] Ultimately, the insulation resistance of the finished cable reached 1.6×10¹³ Ω·m at room temperature, which is 7 times higher than that of Comparative Example 1; and the insulation resistance reached 8.5×10⁹ Ω·m at 350℃, which is 100 times higher than that of Comparative Example 1 and 34 times higher than that of Comparative Example 2.

[0037] Example 2 uses nano-alumina and adds yttrium oxide sintering aid, which further improves high-temperature densification and stability. The insulation resistance at 350℃ reaches 1.1×10¹⁰Ω·m, which is significantly better than the existing technology.

[0038] (III) Microstructure and Mechanism Analysis Grain size testing results show that the process of this invention refines the grain size of Inconel 600 alloy from grade 4.5 in conventional processes to grade 7.5-8.0. Fine grain strengthening is an effective means to improve the strength and plasticity of metallic materials. Simultaneously, uniform and fine grains help reduce radiation-induced grain boundary segregation and radiation hardening, thereby improving radiation resistance. Furthermore, rapid cooling suppresses the continuous precipitation of carbides at grain boundaries, resulting in a dispersed distribution and preventing grain boundary weakening.

[0039] This explains why the strength attenuation rate of the present invention at a high temperature of 350°C is much lower than that of the comparative example.

[0040] In summary, the advantages of this invention compared to the prior art are as follows: by heating and solution treating the nickel-chromium-iron-based alloy tube blank to obtain the outer shell material, the crystals are initially refined. Then, the annealed semi-finished cable is drawn to reduce its diameter. The two processes work together to re-nucleate after each drawing deformation, preventing the grains from being elongated and coarsened in subsequent drawing processes. As a result, the strength attenuation rate of the finished cable at 350℃ is reduced to 14.8%, which is significantly lower than 24.5% in Comparative Example 1 and 18.3% in Comparative Example 2.

[0041] By calcining and removing impurities from alumina powder or nano-alumina powder, and adding yttrium oxide as a sintering aid, impurities and adsorbed water are removed, improving powder flowability. Vibration filling then achieves a filling density of 70%-80%, providing a foundation for subsequent compaction. The semi-finished cable undergoes stress-relief annealing to prevent interfacial thermal stress peeling caused by the difference in cooling shrinkage of the nickel-chromium-iron-based alloy. According to Table 1, although Comparative Example 2 used 1180℃ heating solution treatment and core wire annealing for the nickel-chromium-iron-based alloy tube, it lacked the gradient cooling stress-relief annealing in step 5. Therefore, the insulation resistance at 350℃ was 2.5×10⁸ Ω·m. This indicates that metal heat treatment alone is insufficient to guarantee high-temperature insulation performance; gradient cooling stress-relief annealing targeting the composite interface is necessary. Through these three synergistic processes, taking Example 2 as an example, the final insulation resistance of the finished cable at 350℃ was 1.1×10¹⁰ Ω·m, showing a significant improvement compared to the existing technology in Comparative Example 2.

[0042] By performing stress-relief annealing on semi-finished cables and then heat preservation, followed by a gradient cooling process and a drawing and diameter reduction process, a synergistic heat treatment is carried out. Step 5 first eliminates the residual stress at the interface generated by filling and stranding to prepare for drawing. Then, step 6 involves a cycle of deformation-annealing-re-deformation-re-annealing, which makes the insulating powder denser layer by layer from the outside to the inside. During the processing, the stress is eliminated step by step instead of accumulating at the end, ensuring that the microstructure of the finished cable is uniform and the residual stress is low. This enables the long-term stability of the insulation performance of the finished cable at 350℃, thereby ensuring long-term service stability.

[0043] It is precisely because of the close integration of these steps that a synergistic effect is achieved, resulting in a significant improvement in both mechanical and insulation properties. In terms of mechanical properties, remarkable results have been achieved: the grain size of the nickel-chromium-iron alloy tube and wire has been refined to grade 7.5, increasing the room temperature tensile strength to 575 MPa, a 12.7% improvement compared to Comparative Example 1 and a 5.5% improvement compared to Comparative Example 2. More importantly, the strength attenuation rate at 350℃ has been reduced to 14.8%, significantly lower than the attenuation rates of existing technologies (24.5% for Comparative Example 1 and 18.3% for Comparative Example 2), effectively avoiding the risk of brittle fracture of the cable under long-term thermal cycling and vibration environments.

[0044] Furthermore, significant improvements were achieved in high-temperature insulation performance: ensuring the uniformity and stability of material properties during mass production, reducing residual stress inside the cable, making the product less prone to structural relaxation and insulation degradation under long-term thermal cycling and vibration environments, enhancing interfacial bonding, and achieving a room temperature insulation resistance of 1.6×10¹³ Ω·m and a 350℃ insulation resistance of 8.5×10⁹ Ω·m through a synergistic heat treatment process, which is 7 times higher than that of Comparative Example 1 at room temperature; and 100 times higher than that of Comparative Example 1 and 34 times higher than that of Comparative Example 2 at 350℃.

[0045] In the description of this specification, references to terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0046] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A heat treatment process for armored twisted-pair wires of a self-sufficient neutron detector in a nuclear power plant, characterized in that, The method includes the following steps: Step 1: Heat the nickel-chromium-iron-based alloy tube blank to the solution temperature in an inert atmosphere and hold it at that temperature. After holding at that temperature, cool it to room temperature to obtain the outer shell material. Step 2: Heat the nickel-chromium-iron-based alloy wire in an inert atmosphere and keep it at that temperature to allow the nickel-chromium-iron-based alloy wire to recrystallize and refine the grains, thus obtaining the nickel-chromium-iron-based alloy wire after heat preservation. Cool the nickel-chromium-iron-based alloy wire after heat preservation to room temperature to obtain the core wire material. Step 3: Calcining alumina powder or nano alumina powder to remove impurities, and adding yttrium oxide as a sintering aid for sintering. After sintering, the powder is cooled in the furnace to promote the densification of alumina and obtain an insulating material. Step 4: Twist the core wire material to obtain stranded core wire material. Insert the stranded core wire material into the outer shell material and fill the annular gap between the outer shell material and the core wire material with insulating material to obtain a semi-finished cable. Step 5: Perform stress-relief annealing on the semi-finished cable and keep it warm. After keeping it warm, use a gradient cooling process to release the interfacial stress. After the gradient cooling process, cool it in the furnace to obtain the annealed semi-finished cable. Step 6: The annealed semi-finished cable is subjected to a drawing and diameter reduction process to compact the insulating powder and obtain the finished cable.

2. The heat treatment process for the armored twisted-pair cable of the self-powered neutron detector in a nuclear power plant according to claim 1, characterized in that, In the process of obtaining the outer shell material, the nickel-chromium-iron based alloy tube is made of Inconel 600 alloy material. The heating temperature of the nickel-chromium-iron based alloy tube blank is 1180℃-1220℃, and the inert atmosphere is argon or nitrogen. The holding time in the inert atmosphere is 30-60 minutes to fully dissolve the alloying elements and carbides inside the nickel-chromium-iron based alloy tube blank. After the holding time is completed, it is cooled to room temperature at a rate of 50-80℃ / s to obtain the outer shell material. The microstructure of the outer shell material is a supersaturated solid solution microstructure.

3. The heat treatment process for the armored twisted-pair cable of the self-powered neutron detector in a nuclear power plant according to claim 2, characterized in that, In the process of obtaining the core wire material, the nickel-chromium-iron-based alloy wire is made of Inconel 600 alloy material. The heating temperature of the nickel-chromium-iron-based alloy wire is 880℃-920℃, and the inert atmosphere is argon or nitrogen. The holding time in the inert atmosphere is 15-30 minutes to eliminate cold work hardening and refine the grains. The cooling rate is 20-40℃ / s.

4. The heat treatment process for the armored twisted-pair cable of the nuclear power plant self-sufficient neutron detector according to claim 3, characterized in that, In the process of obtaining insulating materials, when alumina powder is used for calcination and impurity removal, the mass fraction of the alumina powder is 99.5%, the purity of the alumina powder is ≥99%, the calcination temperature is 800℃-1000℃, the calcination time is 1-2 hours, and the mass fraction of yttrium oxide is 0.5%. When using nano-alumina powder for calcination and impurity removal, the mass fraction of the nano-alumina powder is 99.5%, the purity of the alumina powder is ≥99%, the calcination temperature is 800℃-1000℃, the calcination time is 1-2h, and the mass fraction of yttrium oxide is 0.5%.

5. The heat treatment process for the armored twisted-pair cable of the nuclear power plant self-sufficient neutron detector according to claim 4, characterized in that, In step 4, the stranding process of obtaining the stranded core wire material specifically includes: Two to four core wires are twisted together in a bidirectional symmetrical manner, with the twisting pitch set to 8 to 10 times the core wire diameter and the twisting tension set to 0.5 to 2 N, to obtain the twisted core wire material. The stranded core wire material is coaxially inserted into the outer shell material. Insulating material is then filled into the annular gap between the outer shell material and the core wire material using vibration filling or air pressure filling methods, so that the filling density reaches 70-80%.

6. The heat treatment process for the armored twisted-pair cable of the nuclear power plant self-sufficient neutron detector according to claim 5, characterized in that, In the process of obtaining the annealed semi-finished cable, the annealing temperature is 300℃-400℃, the holding time is 1-2h, the cooling rate is 10℃ / min, the cooling temperature is 250℃, and the holding time is 0.5h.

7. The heat treatment process for the armored twisted-pair cable of the nuclear power plant self-sufficient neutron detector according to claim 6, characterized in that, In the process of obtaining the finished cable, the drawing and diameter reduction process specifically includes: The annealed semi-finished cable is subjected to first-stage drawing, middle-stage drawing and final-stage drawing. The annealed semi-finished cable is continuously drawn in the drawing die, and stress-relief annealing is performed in each drawing process.

8. The heat treatment process for the armored twisted-pair cable of the self-powered neutron detector in a nuclear power plant according to claim 7, characterized in that, The diameter reduction rate of the first drawing stage in the drawing reduction process is 20-30%, the diameter reduction rate of the middle drawing stage is 35%, and the total diameter reduction rate of the final stage is 5-15%. After the drawing reduction process, the total diameter reduction rate of the semi-finished cable after annealing is controlled at 60%-80%, and the drawing speed is controlled at 5-15 m / min. After each drawing stage, the cable undergoes intermediate stress-relief annealing at a temperature of 950-1050℃ for a holding time of 0.5-2 h. After the drawing is completed, the insulating powder is compacted to a density ≥85%.